2022
DOI: 10.1111/jfbc.14038
|View full text |Cite
|
Sign up to set email alerts
|

trans‐ferulic acid attenuates hyperglycemia‐induced oxidative stress and modulates glucose metabolism by activating AMPK signaling pathway in vitro

Abstract: Adenosine monophosphate-activated protein kinase (AMPK) is a potent metabolic regulator and an attractive target for antidiabetic activators. Here we report for the first that, trans-ferulic acid (TFA) is a potent dietary bioactive molecule of hydroxycinnamic acid derivative for the activation of AMPK with a maximum increase in phosphorylation (2.71/2.67 ± 0.10; p < .001 vs. high glucose [HG] control) in hyperglycemia-induced human liver cells (HepG2) and rat skeletal muscle cells (L6), where HG suppresses the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 70 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…From the non-triterpene compounds, the cinnamic, benzoic, or fukiic acid derivatives were clearly classified as active. A literature search supported this classification for synaptic acid [ 36 ], P-coumaric acid [ 11 ], isoferulic acid [ 37 ], protocatechuic acid [ 37 ], and protocatechuic aldehyde [ 38 ]. Compounds such as cimiracemates, cimiphenones, cimifugic acid derivatives, and actealactone were likewise classified as active.…”
Section: Resultsmentioning
confidence: 98%
“…From the non-triterpene compounds, the cinnamic, benzoic, or fukiic acid derivatives were clearly classified as active. A literature search supported this classification for synaptic acid [ 36 ], P-coumaric acid [ 11 ], isoferulic acid [ 37 ], protocatechuic acid [ 37 ], and protocatechuic aldehyde [ 38 ]. Compounds such as cimiracemates, cimiphenones, cimifugic acid derivatives, and actealactone were likewise classified as active.…”
Section: Resultsmentioning
confidence: 98%
“…D-gluconic acid has toxin-reducing and antioxidant abilities, wherein it can improve diabetic kidney tubular damage by inhibiting inositol oxygenase, preventing mitochondrial damage and apoptosis and reducing oxidative stress through the ascorbic acid and aldehyde metabolic pathway, thereby improving kidney function [ 38 ]. Moreover, ferulic acid has been shown to lighten oxidative stress through the activation of the AMPK signalling pathway in vitro [ 39 ]. Pipecolic acid is an intermediate in the lysine degradation pathway, with an enhanced lysine degradation pathway indicating enhanced levels of oxidative stress in the host [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased phosphorylation of AMPK, upregulation of GLUT2 and GLUT4, and inhibition of JNK1/2 activity. [128] HUVEC cells incubated in a hyperglycemic medium.…”
Section: Curcuminmentioning
confidence: 99%
“…Hyperglycemia induces oxidative stress and decreases AMPK phosphorylation. Sigh and Patil [ 128 ] showed that trans-FA increased cellular phosphorylation of AMPK in cultured HepG2 and L6 cells exposed to high glucose in a time-dependent manner, besides causing upregulation of GLUT2 and GLUT4 and inhibition of JNK1/2 activity.…”
Section: Dietary Polyphenols: a Potential Strategy For Management Of ...mentioning
confidence: 99%